Insight in cyclopentadienyl metal complexes with superbulky ligands: The crystal structure of [CpBIGK]∞ - Harder, Sjoerd; Ruspic, Christian (Journal of Organometallic Chemistry, 2009)
Reaction of (4-nBu-CH)CpH (=CpH) with KH in THF and subsequent recrystallization from hexane/EtO gave the solvent-free product CpK in good crystalline yield (55%). Crystal structure determination revealed the one-dimensional coordination polymer [CpK]. Despite the steric bulk of the Cp ligands, the chains are not perfectly linear. They can be pictured as an array of highly symmetric (Cp) K sandwiches bridged by K ions at an angle of 167.7(2)°. The C-K bond distances are much shorter than those in other cyclopentadienyl potassium complexes. This is explained by networks of attractive C-H⋯C(π) interactions between neighbouring Cp ligands. In all cases the C-H donors and C acceptors are represented by the ortho-CH units in the aryl substituents. The C-H···C(π) networks within the supersandwich are less distinct than those observed in the metallocene sandwich complexes (Cp)M (M = Ca, Sr, Ba, Yb, Sm). Significant out-of-plane bending of the aryl substituents indicates that, within the supersandwich chain, pairs of tighter C-H⋯C(π) networks exist. Large displacement factors for the K ions are explained by assuming induced polarization of these soft metals. This results in enforcement of the Cp-K interactions. © 2008.